Plasma scale length effects on protons generated in ultra-intense laser–plasmas. (22nd December 2016) - Culfa, O.; Tallents, G.J.; Korkmaz, M.E.; Rossall, A.K.; Wagenaars, E.; Ridgers, C.P.; Murphy, C.D.; Booth, N.; Carroll, D.C.; Wilson, L.A.; Lancaster, K.L.; Woolsey, N.C.
Abstract: The energy spectra of protons generated by ultra-intense (10 20 W cm −2 ) laser interactions with a preformed plasma of scale length measured by shadowgraphy are presented. The effects of the preformed plasma on the proton beam temperature and the number of protons are evaluated. Two-dimensional EPOCH particle-in-cell code simulations of the proton spectra are found to be in agreement with measurements over a range of experimental parameters.